The urgency of stroke prevention after TIA - Johnston, S. Claiborne (Henry Stewart Talks, 2008)
TIA definition, Short-term prognosis after TIA, Predicting risk, Unique pathophysiology, Distinguishing TIA from mimics, Urgent treatment
Archived at 2021/02/25